Synthesis of 2-hydroxy-3-(2-methyl-propenyl)-1,4-naphthoquinone and related oxime derivatives - Patricia S. Oliveira; Celso A Camara (Orbital: The Electronic Journal of Chemistry, 2012)
The condensation reaction of commercial 2-hydroxy-1 ,4-naphthoquinone 1 (lawsone) with isobutyraldehyde 2 furnishs norlapachol 3 (2-hydroxy-3-(2-methyl-propenyl) -1,4-naphthoquinone) with yields ranging from 66 to 93% depending on the different conditions tested, and a reaction temperature factor determinant for the formation of the desired product. It was treated with hydroxylamine hydrochloride in alkaline (NaOH) to provide the oxime 4 from regioselective modification of the carbonyl C-1 with 91% yield. The regioselectivity of the reaction can be explained by analyzing the different resonance structures which can be seen that the carbonyl C-4 is less electrophilic than C-1. In this work was also obtained the oxime 5, 6 and 7 from lapachol, αlpha and β-lapachone, respectively, in yields of 64-85%. The oximes of αlpha and β-norlapachone, 8 and 9 are in obtention. All the products were analyzed by IR and NMR, and were observed that oximes of lapachol and norlapachol are isolated as E/Z mixtures. Two-dimensional NOE-type experiments of the corresponding acylated derivative will be made to help identify the proportion of the mixture.